CHANGES IN THE USE OF LEISURE TIME AT NIGHT IN COLLEGE STUDENTS (CASE STUDY OF PADANG STATE UNIVERSITY STUDENTS) - Mufti Ali; Firman Firman; Rusdinal Rusdinal (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
The utilization of leisure time for every human being is different, it depends on work, habits, environment and many other factors it uses. Likewise with UNP students who use leisure time to do assignments, exercise and many others. The research used qualitative research. The method of data collection in this study also uses Observation, Interview and Documentation methods. The results of this study of the facts resulting from the trial of nighttime free time for unschooled students where there are three clarifications include: (1). Active students take advantage of time to search for lecture materials, lecture assignments, all information available on campus using smart phones, (2). High-class students prefer lifestyles that often sit with friends at a coFfe shop, snack, night club (discotheque), (3). Low-class students are more likely to hang out at the shops that provide free wifi.